From Insect Bites to a Skin Autoimmune Disease: A Conceivable Pathway to Endemic Pemphigus Foliaceus - Li, Ning; Aoki, Valeria; Liu, Zhi; Prisayanh, Phillip; Valenzuela, Jesus G.; Diaz, Luis A. (Frontiers in Immunology, 2022)
In the endemic variants of pemphigus foliaceus (EPF), described in Brazil and Tunisia, patients generate pathogenic IgG4 anti-desmoglein 1 (Dsg1) autoantibodies. Additionally, these patients possess antibodies against salivary proteins from sand flies that react with Dsg1, which may lead to skin disease in susceptible individuals living in endemic areas. This minireview is focused on recent studies highlighting the possible role of salivary proteins from Lutzomyia longipalpis (L longipalpis) in EPF from Brazil and Phlebotomus papatasi (P papatasi) in Tunisian EPF. We will briefly discuss the potential mechanisms of molecular mimicry and epitope spreading in the initiation and development of Brazilian and Tunisian EPF.